MicroRNA-22 Promotes Renal Tubulointerstitial Fibrosis by Targeting PTEN and Suppressing Autophagy in Diabetic Nephropathy - Yingying Zhang; Siqi Zhao; Depei Wu; Xingmei Liu; Mingjun Shi; Yuanyuan Wang; Fan Zhang; Jing Ding; Ying Xiao; Bing Guo (Journal of Diabetes Research)
Renal tubulointerstitial fibrosis (TIF) is a major feature of diabetic nephropathy (DN). There is increasing evidence demonstrating that microRNAs act as key players in the regulation of autophagy and are involved in DN. However, the exact link among microRNAs, autophagy, and TIF in DN is largely unknown. In this study, our results showed that TIF was observed in DN rats together with obvious autophagy suppression. Moreover, microRNA-22 (miR-22) was upregulated and associated with reduced expression of its target gene phosphatase and tensin homolog (PTEN) in both the kidneys of DN rats and high glucose-cultured NRK-52E cells. Intriguingly, induction of autophagy by rapamycin antagonized high glucose-induced collagen IV (Col IV) and α-SMA expression. In addition, ectopic expression of miR-22 suppressed autophagic flux and induced the expression of Col IV and α-SMA, whereas the inhibition of endogenous miR-22 effectively relieved high glucose-induced autophagy suppression and the expression of Col IV and α-SMA in NRK-52E cells. Overexpression of PTEN protectively antagonized high glucose- and miR-22-induced autophagy suppression and the expression of Col IV. Therefore, our findings indicated that miR-22 may promote TIF by suppressing autophagy partially via targeting PTEN and represents a novel and promising therapeutic target for DN.